(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: A C-section is a standard surgical procedure for complications in childbirth to ensure the safety of the mother and the child. There are global C-section rates that are on the rise and in low-risk pregnancies, it can be done without medical need. Objective: The current cross-sectional study aimed to assess the knowledge, attitudes, and practices (KAP) of women regarding C-sections during their antenatal period at a tertiary care hospital in Multan, Pakistan. Material and Method: Using a purposive sampling technique, data were collected from (N=250) pregnant women attending antenatal clinics, M=27.09; SD=5.25). A structured questionnaire was used which included maternal knowledge regarding C-sections, attitude towards this type of delivery, and perceptions in terms of risk and benefits. Results: The study found that prenatal education must address gaps in knowledge that lead to excessive dependency on C-sections. Results emphasize that interventions could help pregnant women make better decisions that will positively impact maternal and fetal outcomes. Future studies should explore how what caregivers say, what culture says, and what the media say affect what women choose and their decision on whether to get a C-section.